Translation and adaptation of functional auditory performance indicators (FAPI) - Karina Ferreira; Adriane Lima Mortari Moret; Maria Cecilia Bevilacqua; Regina de Souza Tangerino Jacob (University of São Paulo, 2011)
Work with deaf children has gained new attention since the expectation and goal of therapy has expanded to language development and subsequent language learning. Many clinical tests were developed for evaluation of speech sound perception in young children in response to the need for accurate assessment of hearing skills that developed from the use of individual hearing aids or cochlear implants. These tests also allow the evaluation of the rehabilitation program. However, few of these tests are available in Portuguese. Evaluation with the Functional Auditory Performance Indicators (FAPI) generates a child's functional auditory skills profile, which lists auditory skills in an integrated and hierarchical order. It has seven hierarchical categories, including sound awareness, meaningful sound, auditory feedback, sound source localizing, auditory discrimination, short-term auditory memory, and linguistic auditory processing. FAPI evaluation allows the therapist to map the child's hearing profile performance, determine the target for increasing the hearing abilities, and develop an effective therapeutic plan. Objective: Since the FAPI is an American test, the inventory was adapted for application in the Brazilian population. Material and Methods: The translation was done following the steps of translation and back translation, and reproducibility was evaluated. Four translated versions (two originals and two back-translated) were compared, and revisions were done to ensure language adaptation and grammatical and idiomatic equivalence. Results: The inventory was duly translated and adapted. Conclusion: Further studies about the application of the translated FAPI are necessary to make the test practicable in Brazilian clinical use.